Kontraktacja buraków cukrowych jako element konkurencyjności gospodarstw rolnych w sferze agrobiznesu - Gonet, Danuta (The Vertical Integration of Sugar Beet as a Competitive Factor of the Agribusiness Firms, 2006)
The article presents the influence of vertical integration on the competitive powers of agricultural farms of the agribusiness firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 257-262